Endoscopic ultrasound, endoscopic sonoelastography, and strain ratio evaluation of lymph nodes with histology as gold standard - Larsen, M. H.; Fristrup, C.; Hansen, T. P.; Hovendal, C. P.; Mortensen, M. B. (Endoscopy, 2012)
Background and study aims: Accurate lymph node staging is essential for the selection of an optimal treatment in patients with upper gastrointestinal cancer. Endoscopic ultrasound (EUS) and fine-needle aspiration (FNA) are considered to be the most accurate method for locoregional staging. Endoscopic sonoelastography (ESE) assesses the elasticity of lymph nodes and has been used to differentiate lymph nodes with promising results. The aim of this study was to evaluate the use of EUS, EUS – FNA, ESE, and ESE-strain ratio using histology as the gold standard.Patients and methods: Patients with upper gastrointestinal cancer who were referred for EUS examination were enrolled if surgical treatment was planned and the patient had a lymph node that was accessible for EUS – FNA and EUS-guided fine-needle marking (FNM). The lymph node was classified using EUS, ESE, and ESE-strain ratio. Finally, EUS – FNA and EUS – FNM were performed. The marked lymph node was isolated during surgery for histological examination.Results: The marked lymph node was isolated for separate histological examination in 56 patients, of whom 22 (39 %) had malignant lymph nodes and 34 (61 %) had benign lymph nodes. There were no complications of EUS – FNM. The sensitivity of EUS for differentiation between malignant and benign lymph nodes was 86 % compared with 55 % – 59 % for the different ESE modalities. The specificity of EUS was 71 % compared with 82 % – 85 % using ESE modalities.Conclusion: The use of the EUS – FNM technique enabled the identification of a specific lymph node and thereby the use of histology as gold standard. ESE and ESE-strain ratio were no better than standard EUS in differentiating between malignant and benign lymph nodes in patients with resectable upper gastrointestinal cancer.